Penerapan Model Problem Based Learning untuk Meningkatkan Keterampilan Membaca Pemahaman pada Peserta Didik Kelas IV Sekolah Dasar - Suci Rahmawati; Dyah Dwi Anugraheni; Shafira Anindyatama; Siti Istiyati; Syarifatul Istiqomah (Universitas Sebelas Maret, 2025)
The objectives of this study are: 1) to represent the application of Problem Based Learning model in developing reading comprehension skill; 2) to develop reading comprehension skill with Problem Based Learning model. Classroom Action Research (CAR) includes qualitative research. Each cycle consists of planning, implementation, observation, and reflection stages. The subjects of this study were 25 female students. The data collection system used was observation, documentation, and test with source and technique triangulation validity test. Miles and Huberman model was used for data analysis. The results showed that students' reading comprehension ability in the pre-action reached an average of 59,60 with classical completeness of 32%. Cycle 1 reached an average of 65,50 with a classical completeness of 52%. Cycle 2 obtained an average score of 76,40 and classical completeness of 72 %. Based on these facts, it can be said that the reading comprehension ability of IVC grade students of SDIT Nur Hidayah Surakarta in the 2024/2025 academic year can be improved by using the Problem Based Learning model.